Preclinical models for the study of pediatric solid tumors: focus on bone sarcomas - Petrescu, D. Isabel; Yustein, Jason T.; Dasgupta, Atreyi (Frontiers in Oncology, 2024)
Sarcomas comprise between 10-15% of all pediatric malignancies. Osteosarcoma and Ewing sarcoma are the two most common pediatric bone tumors diagnosed in children and young adults. These tumors are commonly treated with surgery and/or radiation therapy and combination chemotherapy. However, there is a strong need for the development and utilization of targeted therapeutic methods to improve patient outcomes. Towards accomplishing this goal, pre-clinical models for these unique malignancies are of particular importance to design and test experimental therapeutic strategies prior to being introduced to patients due to their origination site and propensity to metastasize. Pre-clinical models offer several advantages for the study of pediatric sarcomas with unique benefits and shortcomings dependent on the type of model. This review addresses the types of pre-clinical models available for the study of pediatric solid tumors, with special attention to the bone sarcomas osteosarcoma and Ewing sarcoma.